Ferroptosis in Cancer: Epigenetic Control and Therapeutic Opportunities - Roberta Veglia Tranchese; Sabrina Battista; Laura Cerchia; Monica Fedele (Biomolecules)
Ferroptosis, an iron-dependent form of regulated cell death driven by lipid peroxidation, has emerged as a critical pathway in cancer biology. This review delves into the epigenetic mechanisms that modulate ferroptosis in cancer cells, focusing on how DNA methylation, histone modifications, and non-coding RNAs influence the expression and function of essential genes involved in this process. By unraveling the complex interplay between these epigenetic mechanisms and ferroptosis, the article sheds light on novel gene targets and functional insights that could pave the way for innovative cancer treatments to enhance therapeutic efficacy and overcome resistance in cancer therapy.